Local distribution pipelines in nontechnical language - Miesner, Thomas O. (PennWell, 2017)
More than two million miles of local distribution pipelines deliver natural gas to homes, businesses, schools, and hospitals throughout the United States, and many more serve the rest of the world. These small-diameter, low-pressure pipelines serve as a critical link between high-pressure transportation pipelines and end users. This book explains natural gas distribution systems, a vital component in the overall natural gas transportation system, from their humble beginnings delivering "town gas" to handling today's complex urban infrastructure. Benefits for Readers: Knowing what goes on "behind" the City Gate; Understanding the many components required for local distribution pipelines to function properly; Learning how LDCs are managed and operated to assure continual supply; Comprehending the specialized design, engineering, construction, and maintenance of these systems.
Keywords: Gas distribution -- Popular works.; Natural gas pipelines -- Popular works.; elektronické knihy; electronic books